Sams teach yourself beginning programming in 24 hours - Perry, Greg M. (Sams teach yourself in 24 hours series., 2002)
The Sams Teach Yourself in 24 Hours series provides 24 one-hour lessons with structured steps to guide the user through real-world tasks. This book offers novices a guide to programming basics.